2012
DOI: 10.1002/j.1556-6676.2012.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Perfectionism and Anxiety: Differences Among Individuals With Perfectionism and Tests of a Coping‐Mediation Model

Abstract: This study examined the relationship between adaptive and maladaptive perfectionism, anxiety, and coping processes in a sample of 329 undergraduate students. Specifically, participants with adaptive perfectionism had the lowest levels of anxiety, followed by participants with nonperfectionism, and participants with maladaptive perfectionism had the highest levels. Various coping processes mediating the relationship between maladaptive perfectionism and anxiety are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 44 publications
5
69
3
Order By: Relevance
“…In another study, the frequency of avoidant coping style use was significantly related to evaluative concerns and functioned as a mediator for predicting trait anxiety (Gnilka, Ashby, & Noble, 2012). Frequent use of alternative coping styles including distancing, self-controlling, and accepting responsibility was also significantly related to evaluative concerns and functioned as a mediator.…”
Section: Mediational and Moderational Researchmentioning
confidence: 92%
“…In another study, the frequency of avoidant coping style use was significantly related to evaluative concerns and functioned as a mediator for predicting trait anxiety (Gnilka, Ashby, & Noble, 2012). Frequent use of alternative coping styles including distancing, self-controlling, and accepting responsibility was also significantly related to evaluative concerns and functioned as a mediator.…”
Section: Mediational and Moderational Researchmentioning
confidence: 92%
“…Similar findings have been found for categorical perfectionism models. For example, Gnilka, Ashby, and Noble (2012) found that anxiety was highest for maladaptive perfectionists and lowest for adaptive perfectionists, with nonperfectionists falling somewhere in between. By further examining how these dimensions manifest within qualitative data, we hope to better understand the impact of perfectionism in the lives of highly perfectionistic people.…”
Section: What Is Perfectionism?mentioning
confidence: 99%
“…Lazarus & Folkman, 1984). Studies investigating perfectionism and coping have established that perfectionistic concerns show positive correlations with maladaptive coping styles such as avoidant coping and denial whereas perfectionistic strivings show positive correlations with adaptive coping styles such as problem-focused coping and planning (e.g., Dunkley, Blankstein, Halsall, Williams, & Winkworth, 2000;Gnilka, Ashby, & Noble, 2012;Stoeber & Janssen, 2011). In addition, Stoeber and Rennert (2008) found perfectionistic strivings in school teachers to show negative correlations with maladaptive coping.…”
Section: An Intriguing Questionmentioning
confidence: 99%